2020
DOI: 10.12688/f1000research.18721.2
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profiling of anaplastic ependymoma grade III by Ion Proton next generation DNA sequencing

Abstract: Background: Ependymomas are glial tumors derived from differentiated ependymal cells. In contrast to other types of brain tumors, histological grading is not a good prognostic marker for these tumors. In order to determine genomic changes in an anaplastic ependymoma, we analyzed its mutation patterns by next generation sequencing (NGS). Methods:  Tumor DNA was sequenced using an Ion PI v3 chip on Ion Proton instrument and the data were analyzed by Ion Reporter 5.6. Results: NGS analysis identified 19 variants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…Results of a previous study demonstrated a KDR mutation, namely, c.1416A>T; p. (Gln472His) in exon 11, in an anaplastic ependymoma Grade III tumor. In the HBL tumor in this study, c.862T>C; p. (Phe288Leu) was present in exon 7 [20].…”
Section: Gene Name Genotypementioning
confidence: 45%
See 4 more Smart Citations
“…Results of a previous study demonstrated a KDR mutation, namely, c.1416A>T; p. (Gln472His) in exon 11, in an anaplastic ependymoma Grade III tumor. In the HBL tumor in this study, c.862T>C; p. (Phe288Leu) was present in exon 7 [20].…”
Section: Gene Name Genotypementioning
confidence: 45%
“…In the ABL1 gene, a mutation c.864C>T; p. (Ala288Ala; COSM9802919) was detected in the skin, and in the HBL tumor in this study, another mutation in c.864A>T was found that caused the same synonymous change p. (Ala288Ala). Results of a previous study reported intronic PIK3CA (rs3729674) and missense KDR (rs1870377) variants in anaplastic ependymoma Grade III [20]. Notably, synonymous variants found in this tumor were detected in other tumors, such as APC (rs41115) variant in MPE [31], FGFR3 (rs7688609), PDGFRA (rs1873778), and RET (rs1800861) in anaplastic ependymoma Grade III tumor, a-CPP, and myxopapillary ependymoma (MPE) tumors [20,22,23].…”
Section: Gene Name Genotypementioning
confidence: 70%
See 3 more Smart Citations